Biomethanation of sewage sludge by using ultrasonic membrane anaerobic system (UMAS) using sewage sludge as substrate - Nur Sarafina, Samsudin (2015)
This study is going to introduce Ultrasonic Membrane Anaerobic System (UMAS) as an alternative to current conventional methods to solve the problem of membrane fouling. Raw sewage sludge was treated by UMAS which consists of a cross flow ultra-filtration membrane (CUF) apparatus, while pH, pressure, and temperature parameter were kept constant during this experiment with the value of 7.0-7.6, 1.5 bars, and 32OC respectively. Samples has been analyzed for several parameters such as chemical oxygen demand (COD), biochemical oxygen demand (BOD), total suspended solids (TSS), pH, volatile suspended solids (VSS), turbidity and colour, by controlling volatile fatty acids (VFA) and pH parameters. The initial value of COD recorded was 1040 mg/L; BOD was 98.7 mg/L, while TSS and VSS recorded the values of 98.6 mg/L, and 65.8 mg/L respectively. After 28 days of experiment, the final value of COD became 92 mg/L, BOD value dropped to 4.1 mg/L, TSS had final value of 6.0 mg/L while VSS dropped to 4.2 mg/L. The findings are this ultrasonicated-membrane technology has overcome fouling membrane, shorten the retention time of the sewage sludge treatment, reduce the treatment area, and high removal efficiency of Chemical Oxygen Demand (COD), Biochemical Oxygen Demand (BOD) and Total Suspended Solids (TSS). The complete treatment reduced the COD content to 92 mg/L equivalent to a reduction of 91% reduction from the original, while TSS and VSS removal efficiency have reached up to 93%. The final product is Methane (CH4) biogas, ranged from 79% to 96% which become a highly-demand in energy resource, at the same time this technology can reduce the greenhouse effect and global warming caused by the methane gas